Postpartum uptake of diabetes screening tests in women with gestational diabetes: The PANDORA study. Issue 3 (21st November 2022) - Wood, Anna J.; Lee, I‐Lynn; Barr, Elizabeth L. M.; Barzi, Federica; Boyle, Jacqueline A.; Connors, Christine; Moore, Elizabeth; Oats, Jeremy J. N.; McIntyre, Harold D.; Titmuss, Angela; Simmonds, Alison; Zimmet, Paul Z.; et al.
Abstract: Aims: To determine rates and predictors of postpartum diabetes screening among Aboriginal and/or Torres Strait Islander and non‐Indigenous women with gestational diabetes mellitus (GDM). Methods: PANDORA is a prospective longitudinal cohort of women recruited in pregnancy. Postpartum diabetes screening rates at 12 weeks (75‐g oral glucose tolerance test (OGTT)) and 6, 12 and 18 months (OGTT, glycated haemoglobin [HbA1C ] or fasting plasma glucose) were assessed for women with GDM ( n = 712). Associations between antenatal factors and screening with any test (OGTT, HbA1C, fasting plasma glucose) by 6 months postpartum were examined using Cox proportional hazards regression. Results: Postpartum screening rates with an OGTT by 12 weeks and 6 months postpartum were lower among Aboriginal and/or Torres Strait Islander women than non‐Indigenous women (18% vs. 30% at 12 weeks, and 23% vs. 37% at 6 months, p < 0.001). Aboriginal and/or Torres Strait Islander women were more likely to have completed a 6‐month HbA1C compared to non‐Indigenous women (16% vs. 2%, p < 0.001). Screening by 6 months postpartum with any test was 41% for Aboriginal and/or Torres Strait Islander women and 45% for non‐Indigenous women ( p = 0.304). Characteristics associated with higher screening rates with any test by 6 months postpartum included, insulin use in pregnancy, first pregnancy, not smoking and lower BMI. Conclusions: Given very high rates of type 2 diabetes among Aboriginal and Torres Strait Islander women, early postpartum screening with the most feasible test should be prioritised to detect prediabetes and diabetes for intervention.